A short essay on the literature review of the service supply chain - Yun-Jin Kim; Byoung-Chun Ha; Yong-Jeong Kim (Global Business & Finance Review (GBFR), 2023)
Purpose: This study aimed to examine the concrete type of service supply chain, which has been remaining on a conceptual level in previous studies. For this purpose, this study analyzed the differentiation of service supply chain, which could be hardly explained by the traditional manufacturing supply chain architecture. Design/methodology/approach: The research method was conducted through in-depth literature review. It was intended to identify the structure and characteristics of the service supply chain through an in-depth literature review in the service and supply chain fields. Findings: The service industry is made up of a wide range of fields and has various characteristics. The characteristics of the service industry are expected to be more diverse and complicated depending on the tangibility spectrum or servitised degree of the combination of tangible products and intangible services. According to the literature review, remarkable differences were shown between the type of the traditional manufacturing-oriented supply chain and that of the logistics service supply chain in respect of industrial architecture and direction of the entities in the supply chain. Research limitations/implications: This study cannot suggest general service supply chain types through literature review. The reason may be that it was difficult to generalize the types of service supply chains due to the diversity of the service industry and the characteristics of services that are different from tangible products. It was also difficult to apply the methodology to scientifically distinguish service supply chain to the traditional supply chain. Originality/value: The research results of this study on the service supply chain are meaningful in both academic and practical aspects. Academically, it provides the foundation for research on the service supply chain structure. In practice, it suggests the possibility that service companies can also use supply chain management as a business strategy.
Keywords: 650; Service supply chain; Service science; Literature review